A role for Id2 in regulating photic entrainment of the mammalian circadian system. - Duffield, G; Watson, N; Mantani, A; Peirson, S; Robles-Murguia, M; Loros, J; Israel, M; Dunlap, J (2009)
Inhibitor of DNA binding genes (Id1-Id4) encode helix-loop-helix (HLH) transcriptional repressors associated with development and tumorigenesis [1, 2], but little is known concerning the function(s) of these genes in normal adult animals. Id2 was identified in DNA microarray screens for rhythmically expressed genes [3-5], and further analysis revealed a circadian pattern of expression of all four Id genes in multiple tissues including the suprachiasmatic nucleus. To explore an in vivo function, we generated and characterized deletion mutations of Id2 and of Id4. Id2(-/-) mice exhibit abnormally rapid entrainment and an increase in the magnitude of the phase shift of the pacemaker. A significant proportion of mice also exhibit disrupted rhythms when maintained under constant darkness. Conversely, Id4(-/-) mice did not exhibit a noticeable circadian phenotype. In vitro studies using an mPer1 and an AVP promoter reporter revealed the potential for ID1, ID2, and ID3 proteins to interact with the canonical basic HLH clock proteins BMAL1 and CLOCK. These data suggest that the Id genes may be important for entrainment and operation of the mammalian circadian system, potentially acting through BMAL1 and CLOCK targets.